PENGARUH DARI PENGGUNAAN TEKNIK STORYTELLING PADA KEMAMPUAN BERBICARA SISWA KELAS SATU DI SMAN 2 PEKANBARU - Erdiyanti, Esti Purwaningsih; Delfi, Syofia; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research is to know the effect of storytelling technique on studentâs speaking ability of first year students of SMAN 2 Pekanbaru. This research was pre-experimental design involving 36 students as a sample chosen through cluster random sampling. The data were gained after before and after the treatment implementing storytelling technique. The students were given pre-test and post-test. The result of this research shows that storytelling technique had an effect to studentâs speaking ability because there was a significant difference between the post-test and pre-test. It shows that the storytelling technique could help the students to improve their speaking ability. This research suggests that the students should read and speak more to improve their speaking ability.Keywords: Effect, Ability, Storytelling.